Regulation of Natural Monopolies in Kazakhstan - Potluri, Rajasekhara Mouly; T., Myltykbayeva A.; E., Sopbekova N. (Farabi Journal of Social Sciences, 2019)
Abstract. The paper aims to describe and to evaluate a mechanism of regulation of natural monopolies and tariff regulation in the Republic of Kazakhstan. Acknowledgement of the role of natural monopolies in the modern world has generated a large number of theoretical and applied researches. The nature of the regulation of natural monopolies and its role in competitive advantages formation are the subject under consideration in Totev (1995), Kudinov (2003), Butyrkin (2003), Gorodeckiy, Pavlenko (2000), Dzhaksybekova (1999), Sagiyeva R.K.studied natural monopolies and their regulation processes at national and regional levels. The existence of a natural monopoly is justified by the fact that they give a huge economic benefit from large economies of scale.A monopoly is a business or organization that maintains exclusivity of the supply of a particular product or service, and can evolve naturally or be designed specifically based on the nature of a particular market or industry(The Linux Information Project).